Internalization of National Defense Values and Formation of Social Conformity in Makassar City - Rahmatullah; Syamsu A Kamaruddin; Arlin Adam; Arifuddin Usman; Ahmad Restani Syukron (Cita konsultindo, 2025)
This study aims to analyze the design, internalization, conformity values, and community involvement in National Defense Education and Training in Makassar City, particularly among street communities. Using a qualitative approach, this study involved street children (parking attendants, pa'ogah, and buskers) with data collection techniques in the form of interviews, observations, and documentation through Focus Group Discussions (FGD). The results show that effective training design must be inclusive and contextual to foster positive conformity, not coercion. The internalization of national defense values is successful through equal interaction, where respondents' self-efficacy and motivation increase when they feel valued. The conformity that is formed is pro-social, manifested in concrete actions such as mutual cooperation and social awareness, born out of consciousness, not obedience. Finally, the active involvement of all levels of society is the key to the success of the program, fostering a sense of collective responsibility and ownership. This study concludes that the internalization of national defense is effective when it is participatory and relevant to social reality